In-Depth Study into Polymeric Materials in Low-Density Gastroretentive Formulations - Nieves Iglesias; Elsa Galbis; Lucía Romero-Azogil; Elena Benito; Ricardo Lucas; M. Gracia García-Martín; M.-Viola (MDPI AG, 2020)
The extensive use of oral dosage forms for the treatment of diseases may be linked to deficient pharmacokinetic properties. In some cases the drug is barely soluble; in others, the rapid transit of the formulation through the gastrointestinal tract (GIT) makes it difficult to achieve therapeutic levels in the organism; moreover, some drugs must act locally due to a gastric pathology, but the time they remain in the stomach is short. The use of formulations capable of improving all these parameters, as well as increasing the resident time in the stomach, has been the target of numerous research works, with low-density systems being the most promising and widely explored, however, there is further scope to improve these systems. There are a vast variety of polymeric materials used in low-density gastroretentive systems and a number of methods to improve the bioavailability of the drugs. This works aims to expedite the development of breakthrough approaches by providing an in-depth understanding of the polymeric materials currently used, both natural and synthetic, their properties, advantages, and drawbacks.